(untitled) - Zarnay, Pavel; Moravcik, Jozef (Doprava a spoje, 2010)
Changes in the law No. 338/2000 about inland shipping, practical experience from its application and proposals for adjustment. Positions and efforts of the State shipping administration by preparation of the national General plan of water transport development till year 2013 with continuity to implementation of the Action and development program for inland shipping and waterways in Europe (NAIADES).